2018
DOI: 10.1080/01676830.2018.1464584
|View full text |Cite
|
Sign up to set email alerts
|

Evisceration with autogenous scleral graft and bioceramic implantation within the modified scleral shell: 133 cases over 17 years

Abstract: Evisceration with autogenous scleral grafting and ceramic implantation can result in a high volume of restoration, good cosmetic results, and low risk of exposure of the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Unfortunately, in both cases treated with this technique, resorption of the scleral transplant, atrophy of the overlying Te-nonʼs, and conjunctiva occurred. It remains unclear why these complications occurred, and it is surprising since a recently published comparable technique by Nadal et al [6], using autograft sclera from the posterior pole to close the anterior sclera resulted in a low extrusion rate of only 1.5 %. Oversize of implanted spheres can be excluded as a probable cause of failure since both implants (20 mm, 18 mm) were smaller than suggested by the algorithm of Kaltreider and Lucarelli [3] (21 mm in P1 and P2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in both cases treated with this technique, resorption of the scleral transplant, atrophy of the overlying Te-nonʼs, and conjunctiva occurred. It remains unclear why these complications occurred, and it is surprising since a recently published comparable technique by Nadal et al [6], using autograft sclera from the posterior pole to close the anterior sclera resulted in a low extrusion rate of only 1.5 %. Oversize of implanted spheres can be excluded as a probable cause of failure since both implants (20 mm, 18 mm) were smaller than suggested by the algorithm of Kaltreider and Lucarelli [3] (21 mm in P1 and P2).…”
Section: Discussionmentioning
confidence: 99%
“…On the background of the observed complications, our previously described method of modified evisceration cannot be recommended. The recently described technique of Nadal et al [6] indicates that the principle of an anterior scleral graft may still be a promising approach and can probably be performed with very favourable results after modification of some surgical details.…”
Section: Discussionmentioning
confidence: 99%
“…Vzhledem k velmi dobrým výsledkům těchto operací a relativně častým extruzím hlavně u některých typů orbitálních implantátů (zejména implantáty z hydroxyapatitu) Soll v roce 1974 publikoval svou práci, ve které popisuje velmi dobré výsledky při krytí orbitálních implantátů sklerální záplatou už při primární operaci [104]. I tato technika se uchytila a v následujících letech publikovali své výsledky mnozí další autoři [105][106][107][108][109][110]. Vzácnější možnost využití skléry u pacientů po enukleaci popsal v roce 1983 Smith, které ji využil jako výplňový materiál při atrofii tkání očnice [111].…”
Section: Okuloplastická Chirurgieunclassified
“…Gawdat and Ahmed 10 performed additional scleral patch graft followed by the closure of the tenon capsule and conjunctiva in separate layers and found no exposure among 30 patients during 4 years of follow-up. Nadal et al 93 reported excellent outcomes in evisceration with autogenous scleral grafting and ceramic implantation. Park et al 94 described the use of an acellular dermal allograft in patients with insufficient conjunctiva to cover the sclera and implant in a tension-free manner.…”
Section: Surgical Technique Of Eviscerationmentioning
confidence: 99%